FACIES DISTRIBUTION OF THE LOWER CAMBRIAN CRYPTIC MICROBIAL AND EPIBENTHIC ARCHAEOCYATHAN-MICROBIAL COMMUNITIES, WESTERN ANTI-ATLAS, MOROCCO - Álvaro J.J.; Clausen S.; El Albani A.; Chellai E.H. (My University, 2006)
Marine microbial communities recorded in the Moroccan Anti-Atlas were unaffected across the Neoproterozoic-Cambrian transition. A stromatolitedominated consortium was replaced at the beginning of the Atdabanian (ca 20 Myr after the Neoproterozoic-Cambrian boundary) by shelly metazoan and thromboid consortia, which contain the oldest biostratigraphically significant fossils of the Moroccan Cambrian. The associated collapse of microbial mat (stromatolitic) growth appears to coincide with a change from pre-Atdabanian shallow-water restricted conditions into Atdabanian deeper, open-sea conditions. It is postulated that this environmental change led to an episode of improved water circulation over carbonate platform interiors, promoting shelly metazoan immigration into the region. The Tiout/Amouslek lithostratigraphic contact in the early Atdabanian marks the end of an episodically unstable seafloor as suggested by the abundance of slumping and sliding structures, and synsedimentary microfaults and cracks recorded in the underlying Tiout Member. Concurrent with the transition is the occurrence of a network of cryptic fissures and cavities that provided habitats for a coelobiontic chemosynthetic-heterotrophic microbial community composed of stromatolitic crusts, Renalcis-Epiphyton-Girvanella intergrowths, and Kundatia thalli. In the overlying Amouslek Formation, archaeocyathan- thromboid reefs were constrained by substrate stability, water depth and subsidence rate. Four reef geometries are distinguished: (i) patch reefs surrounded by shales, (ii) bioherms in which flank beds intercalate laterally with carbonate and shale inter-reef sediments, (iii) biostromes or low-relief structures formed as a result of lateral accretion of patch reefs, and (iv) kalyptrate complexes that nucleated because of a marked tendency for aggregation, and in which patch reefs and bioherms occur stacked together bounded by clay-marl-silt seams. © 2005 International Association of Sedimentologists.
Keywords: ANTI-ATLAS; BENTHIC REPLACEMENT; CRYPTIC CAVITIES; LOWER CAMBRIAN; MICROBIALITES; REEFS; Cambrian; Neoproterozoic; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская